2013
DOI: 10.5114/pjp.2013.39339
|View full text |Cite
|
Sign up to set email alerts
|

The role of the 148 Asp/Glu polymorphism of the APE1 gene in the development and progression of primary open angle glaucoma development in the Polish population

Abstract: Glaucoma is an ocular disorder that is characterized by progressive degeneration of the optic nerve and loss of visual field (VF). Recent data have suggested that the level of oxidative DNA damage in human trabecular meshwork is significantly increased in glaucomatous patients as compared to controls. It was also noted that progressive loss of visual field may by connected with elevated levels of oxidative DNA lesions. This hypothesis may suggest the role of an inefficient base excision repair pathway in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(23 reference statements)
2
3
0
Order By: Relevance
“…The results of our data confirmed our preliminary study's results that presented a lack of association between this gene and the risk of POAG development [63].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The results of our data confirmed our preliminary study's results that presented a lack of association between this gene and the risk of POAG development [63].…”
Section: Discussionsupporting
confidence: 94%
“…Such a composition of research allows us to assess which stage of BER might play a crucial role in pathogenesis and whether the screened SNPs may potentially disturb BER. Our results herein enhanced our preliminary study regarding the role of SNPs in the pathogenesis of POAG [48,63]. Thus, it can be noted that POAG patients have decreased BER repair capacity.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…94,95,104,121 The pooled results showed that rs1799750 was significantly correlated with POAG in recessive model (OR 1.64, 95% CI: 1.05-2.56; P ¼ 0.01, I 2 ¼ 73. 90). No evidence of association was observed in rs3918242 in the MMP gene 94,95 (Table 2, Supplementary Files S7).…”
Section: Meta-analysis Of the Genetic Association With Poagmentioning
confidence: 97%
“…For SNP 148Asp/Glu in the APE1 gene, two studies (562 POAG cases and 644 controls) were involved. 74,90 Significant association was found between this SNP and POAG risk in homozygote (OR 5.91, 95% CI: 1.24-28.17; P ¼ 0.85, I 2 ¼ 0.00) and recessive models (OR 5.26, 95% CI: 1.12-24.82; P ¼ 0.85, I 2 ¼ 0.00), but not in allelic, heterozygote, or dominant models ( Table 2, Supplementary Files S4).…”
Section: Meta-analysis Of the Genetic Association With Poagmentioning
confidence: 99%